Incorporating efl pre-reading comprehension strategies: skimming and using the prior knowledge in the sixth-b graders at Nuestra Señora de Fatima Cali school ﻿ (2016)
This paper aims to report a research carried out with sixth-B graders at Nuestra Señora de Fatima Cali school. Its objectives were to describe the reading process and the effects of the implementation of EFL pre-reading comprehension strategies: skimming and prior knowledge. The type of research designed was action research which allows teachers to keep track and take into account many aspects of their work with students through a systematic routine following the characteristics of a qualitative study. Data were gathered through observation of the students utilizing teacher reflective journal, student‘s survey (questionnaire applied before the pedagogical proposal and oral interview applied in the final of the application of EFL pre-reading comprehension workshops) and students’ artifacts. Considering the data collected, this study determines that teaching EFL pre-reading comprehension strategies (skimming and prior knowledge) through the pedagogical approaches top down, bottom up allows the students to identify the gist in a text, locate specific information and relate the text with the real context. As an implication teachers need to provide these strategies to activate their students’ prior knowledge. They can use it teaching previewing vocabulary or formulating questions about what the students know about the topic they are going to read. Teachers need to teach students to identify and analyze the key elements in a text which allows to obtain the overall idea and they will not be all the time looking up the dictionary. Also it is necessary to look through the student’s texts before they read to know the context and its level of the materials.